Three-dimensional Si / vertically oriented graphene nanowalls composite for supercapacitor applications. Issue 15 (1st August 2021) - Hussain, Shahzad; Amade, Roger; Boyd, Adrian; Musheghyan-Avetisyan, Arevik; Alshaikh, Islam; Martí-Gonzalez, Joan; Pascual, Esther; J. Meenan, Brian; Bertran-Serra, Enric
Abstract: Three-dimensional (3D) carbon nanostructures are promising architectures to improve both specific capacity and power density of electrochemical energy storage systems. Their open structure and porosity provide a large space for active sites and high ion diffusion rates. To further increase their specific capacity, they can be combined with metal oxides. However, this combination often results in the loss of cycling stability and power density. Among the different electrode materials being studied, vertically oriented graphene nanowalls (VG) have recently been put forward as a potential candidate. Here, we report the use of VG covered by Si for increased supercapacitor performance. VG were grown on flexible graphite sheet (FGS) substrate by inductively coupled plasma chemical vapor deposition (ICP-CVD). Furthermore, silicon (Si) was deposited by magnetron sputtering on VG and the electrochemical performance studied in ionic liquid (IL) electrolyte. The incorporation of Si in VG/FGS provides an areal capacitance up to 16.4 mF cm −2, which is a factor 2 and 1.4 greater than that of bare substrate and VG/FGS, respectively. This increase in capacitance does not penalize the cycling stability of Si/VG/GS, which remains outstanding up to 10, 000 cycles in IL. In addition, the relaxation time constant decreases from 9.1 to 0.56 ms after Si deposition on VG/FGS. Graphical abstract: Image 1